THE INFLUENCE OF GIVING COMPENSATION ON EMPLOYEE PERFORMANCE PRODUCTIVITY AT ARIFA MART - Zaky, O K M; Irvan, Irvan; Amelia Sari Br.S . Pane, Lola; Balqis, Putri; Nur Ilham, Rico (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
Over time, micro, small and medium enterprises or cooperatives will develop rapidly in the future as they are today, many people are willing to open micro, small and medium enterprises. From several places we visited, we got one of the micros, small and medium enterprises, precisely in Blang Pulo, called ARIFA MART. The ARIFA MART business itself has been established since 2017 which is located in Blang Pulo. The name ARIFA MART is also taken from the names of people, namely Arif, Anis, Fatlan. The number of Arifa Mart employees is 25 people, starting from cashiers, goods carriers, and outside guards. With 25 employees, Arifa Mart does 2 work shifts morning – afternoon and afternoon – evening. Arifa Mart has been running its business for about 6 years now, with never a few visitors, Arifa Mart is also well known among the public or students. The method used in this research is quantitative. The results of this study, it can be concluded that more compensation will be given if the employee can work with high loyalty.